Pemetaan Faktor Risiko Preeklampsia berbasis Sistem Informasi Geografis (SIG) di Puskesmas Kendit Kabupaten Situbondo - Maulana, Achmad Ilham; Ramani, Andrei (Pustaka Kesehatan, 2024)
Preeclampsia is a compilation of symptoms occurring in pregnant, delivering, and postpartum women, typically characterized by hypertension, edema, and proteinuria from the 20th week of pregnancy until the end of the first week postpartum. Risk factors for preeclampsia include maternal age >35 years, maternal age <20 years, primigravida, a history of hypertension, adherence to Antenatal Care (ANC), obesity, and a history of preeclampsia. Priority scaling is essential in the development of prevention and management programs for Acute Kidney Injury (AKI), particularly preeclampsia. One method to prioritize program development is mapping potential issues in a region through a Geographic Information System (GIS) approach. This research aims to illustrate the distribution of preeclampsia risk factors in the working area of Kendit Primary Health Center. The research method utilized is quantitative descriptive. The results indicate that the areas with very high-risk categories for preeclampsia and maternal age are in Rajekwesi Village, with a very high prevalence of obesity and hypertension history risk factors in Tambak Ukir Village, a very high prevalence of a history of preeclampsia risk factor in Klatakan Village, a very high prevalence of primigravida risk factor in Bugeman Village, and no cases of adherence to antenatal care <4 times in the working area of Kendit Primary Health Center.